A rectenna as energy source for wireless sensor nodes. - Contreras, Andry (2020)
This paper presents the feasibility assessment for the adoption of a rectenna with basic structure elements as energy source in wireless sensor networks (WSN) nodes. For that matter, a rectenna that harvests energy from 2.45 GHz was designed by the application of a tuning technique on the dimensions of its elements. In the design, the CST Microwave Studio and a SPICE based software were used. The DC-DC boost converter was selected among several commercial options. The limitations of the rectenna were evaluated using the power consumption of different nodes. Results show that the total maximum conversion efficiency for the rectenna was 34.08% at 20 dBm. The distance ranges between the designed rectenna and the wireless energy source were from 0.03 m to 0.20 m in the indoor scenario and from 0.26 m to 2.03 m in the outdoor scenario. The rectenna can supply the required power for the nodes CC2538 and CC1350 in the full range of distances, but for the nodes Z1 and Sky the range of distances is reduced.